Peer effects in sexual initiation: Separating demand and supply mechanisms - Seth Richards-Shubik (Quantitative Economics, 2015)
Most work on social interactions studies a single, composite effect of interactions within a group. Yet in the case of sexual initiation, there are two distinct social mechanisms—peer-group norms and partner availability—with separate effects and different potential interventions. Here I develop an equilibrium search and matching model for first sexual partners that specifies distinct roles for these two mechanisms as part of demand and supply. I estimate the model using a national sample of high school students, with data over time on individual virginity status. The results indicate that peer-group norms have a large effect on the timing of sexual initiation for both boys and girls. Changes in opposite-gender search behavior (i.e., partner availability) also have a large impact on initiation rates for boys, but not for girls.
Keywords: 330; Social interaction models; mechanisms; sexual activity; youth; structural estimation